Consuming the Caribbean: from Arawaks to Zombies - Sheller, Mimi (USA; Routledge, 2003)
Consuming the Caribbean demonstrates how colonial exploitation of the Caribbean led directly to contemporary forms of consumption of the region and its products. It calls into question innocent indulgence in the pleasures of thoughtless consumption and calls for a global ethics of consumer responsibility. From sugar to indentured labourers, tobacco to reggae music, Europe and North America have been relentlessly consuming the Caribbean and its assets for the past five hundred years. In this fascinating book, Mimi Sheller explores this troublesome history, investigating the complex mobilities of producers and consumers, of material and cultural commodities.
English
Keywords: HF3000-4055 Commerce- By region or country; Caribbean